Immunophenotype Characteristics of Peripheral Blood Mononuclear Leukocytes of Chronic Idiopathic Urticaria Patients - Garmendia, Jenny V; Zabaleta, Mercedes; Aldrey, Oscar; Rivera, Henry; De Sanctis, Juan B; Bianco, Nicolás E; Blanca, Isaac (Investigación Clínica, 2009)
The pathogenesis of chronic idiopathic urticaria (CIU) is not completely understood although autoimmunity has been proposed. The aim of the study was to assess the expression of different leukocyte antigens, by flow cytometry, assaying total blood of 29 patients with CIU and of 20 sex and age matched controls. Moreover, we assessed soluble CD154 a marker of immune cell activation, predominantly memory T cells. When patients were divided depending an their response to the autologous serum skin test (ASST), three different groups were encountered: group 1 (n = 11): with negative ASST ”“, group 2 (n = 11): positive ASST (ASST +) with normal lymphocyte counts and group 3 (n = 7): ASST + with low lymphocyte counts (< 1500 cells/mm3). A significant increase in CD19+ percentage and not in the absolute count (P < 0.05) was observed in group 1 as compared to controls and to the other groups. In contrast, CD30+, CD45RO+ and CD4+/CD45RO+ percentages and biologically active soluble CD154 levels were significantly higher (P < 0.05) in group 3 as compared to group 1 or to controls. In ASST positive groups, CD45RO+ and CD4+/CD45RO+ positiveness correlates with wheal diameter. In conclusion, memory cells may play a role in these different types of patients and in understanding CIU pathogenesis